2022
DOI: 10.3389/fneur.2022.910259
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Machine Learning for Tissue Outcome Prediction in Acute Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: Machine learning (ML) has been proposed for lesion segmentation in acute ischemic stroke (AIS). This study aimed to provide a systematic review and meta-analysis of the overall performance of current ML algorithms for final infarct prediction from baseline imaging. We made a comprehensive literature search on eligible studies developing ML models for core infarcted tissue estimation on admission CT or MRI in AIS patients. Eleven studies meeting the inclusion criteria were included in the quantitative analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Several studies support that ML can predict stroke prognosis more accurately (17)(18)(19). Wang et al (20) showed that, despite variability, current ML-based prognosis prediction of stroke patients has great potential. Qu et al (21) used ML of retinal images to assess risk in 771 patients with ischemic and hemorrhagic stroke, achieving sensitivity and specificity of ischemic stroke risk assessment values of 91.0 and 94.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies support that ML can predict stroke prognosis more accurately (17)(18)(19). Wang et al (20) showed that, despite variability, current ML-based prognosis prediction of stroke patients has great potential. Qu et al (21) used ML of retinal images to assess risk in 771 patients with ischemic and hemorrhagic stroke, achieving sensitivity and specificity of ischemic stroke risk assessment values of 91.0 and 94.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…ML not only offers promising applications in medical imaging by learning information features and patterns from structured input data, but also promotes the emergence of deep learning (DL) and demonstrates its excellent performance in medical image processing ( 79 , 80 ). XinruiWang's latest study ( 81 ) analyzed ML models to predict the volume of core infarct tissue in AIS patients based on basic CT or MRI imaging at admission. DL models outperformed traditional ML classifiers, with the best performance observed in DL algorithms combined with CT data.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [30] discussed some state-of-the-art lesion segmentation techniques. They concluded that multi-centre data might be required to improve the performance of the AI-based models.…”
Section: Previous Literature Surveysmentioning
confidence: 99%